Evaluating the effectiveness of Thiel embalming solution for preserving cadavers in anatomy and surgical education - I Made Rayo Putra Indrawan; Ria Margiana (Universitas Muhammadiyah Surabaya, 2025)
Cadavers have played a crucial role in anatomy teaching, owing to their resemblance to the anatomical structures found in living individuals. To optimize the utilization of cadavers, embalming procedures that involve the application of chemical fixative agents are needed. The